Sustainable Rice Platform (SRP) Standard and Performance Indicators in Africa - CGIAR Research Program on Rice (2021)
SRP standard and performance indicators were assessed in Burkina Faso, Ghana, Nigeria, Senegal, and Tanzania. In Senegal, based on the results from the assessment, training on sustainable rice cultivation was conducted to a total of 575 farmers including 162 women. Impact of training is under evaluation.